The use of recycled corrugated iron as efficient electrodes in a batch electrocoagulation treatment process for the removal of algal and bacterial nutrients from raw water - Siyanda Yamba; Nomso C. Hintsho-Mbita; Nonhlangabezo Mabuba (Case Studies in Chemical and Environmental Engineering)
The presence of ammonia, nitrates and phosphates in raw water promotes the excessive growth of toxic algal blooms which reduce water quality and cause health risks to aquatic and human life. Hence, batch electrocoagulation parameters were optimized (15V, pH 6, 40 mg/l and 20 min) to remove algal nutrients using a recycled corrugated electrode (50 mm × 150 mm x 0.3 mm) in raw water. The electrode was characterized using FTIR, SEM and EDS. It removed 99 ± 0.6 %, 98 ± 05 %, 89 ± 0.3 %, above 99 % of phosphate, nitrate, ammonia, and bacteria respectively. Electrocoagulation is efficient, removes chemicals, bacteria and it is inexpensive.